2021
DOI: 10.3390/agronomy11122485
|View full text |Cite
|
Sign up to set email alerts
|

Sensor-Based Irrigation Reduces Water Consumption without Compromising Yield and Postharvest Quality of Soilless Green Bean

Abstract: Real-time monitoring of substrate parameters in the root-zone through dielectric sensors is considered a promising and feasible approach for precision irrigation and fertilization management of greenhouse soilless vegetable crops. This research investigates the effects of timer-based (TIMER) compared with dielectric sensor-based irrigation management with different irrigation set-points [SENSOR_0.35, SENSOR_0.30 and SENSOR_0.25, corresponding to substrate volumetric water contents (VWC) of 0.35, 0.30 and 0.25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…At the end of storage, the highest value of total phenols was observed in ScS-LF leaves (85.30 ± 2.02 mg gallic acid/100 g fw). These results prove the existence of a positive correlation between total phenols and antioxidant activity, as already reported for many fruit and vegetables [ 30 , 59 ], confirming that phenols highly contribute to the antioxidant activity of the product. In the present study, a significant increase in phenolic compounds was induced by low concentrations of nutrients in accordance with [ 23 ], which reported similar results for rocket leaves cultivated in a soilless system.…”
Section: Resultssupporting
confidence: 87%
“…At the end of storage, the highest value of total phenols was observed in ScS-LF leaves (85.30 ± 2.02 mg gallic acid/100 g fw). These results prove the existence of a positive correlation between total phenols and antioxidant activity, as already reported for many fruit and vegetables [ 30 , 59 ], confirming that phenols highly contribute to the antioxidant activity of the product. In the present study, a significant increase in phenolic compounds was induced by low concentrations of nutrients in accordance with [ 23 ], which reported similar results for rocket leaves cultivated in a soilless system.…”
Section: Resultssupporting
confidence: 87%
“…Compared to timer-based irrigation, sensor-based irrigation may considerably reduce water consumption and increase WUE, providing water (and fertilizers) on-demand just when plants require it and reducing the drainage fraction to minimum values (<10%). In previous studies recently conducted, increases in WUE, ranging from 25 to 70%, were observed with sensor-based compared to timer-based irrigation management for several horticultural crops, including lettuce [20], basil [19], green bean and rocket [13,14]. In the case of strawberry, an experiment conducted in Korea to investigate the potential application of an irrigation schedule based on FDR sensors and VWC measurement showed that the total irrigation volume was 1.7-fold higher with the timer-based than with sensor-automated irrigation, with no differences in terms of plant growth, fruit yield and soluble solid content [21].…”
Section: Introductionmentioning
confidence: 93%
“…Significant water savings are generally observed with soil moisture-based methods compared to other scheduling methods [28]. With specific reference to greenhouse vegetables, several recent studies confirm lower irrigation consumption with sensor-based compared to timer-based irrigation management [13,14,23].…”
Section: Irrigation Consumption Vwc and Ecmentioning
confidence: 99%
See 1 more Smart Citation
“…Practical empathy is the foundation of cultural empathy, and cultural empathy is the superstructure of practical empathy, and there is both a bottom-up and top-down logical relationship between the above two. Consumers buy classical furniture products to meet their consumption needs, which can be based on a lower level of material need arising from the product itself which is the lowest level of needs or a higher level of the spiritual need arising from the product culture ( Palumbo et al, 2021 ). Only when consumers’ practical material needs are satisfied can they seek to satisfy their cultural spiritual needs ( Lienert, 2015 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%